Psycho-Linguistic Changes Associated With Historical Celebrities in Henan Using Classical Chinese Big Data - Zhao, Yanan; Xing, Fugui; Fan, Miaorong; Li, Hua; Zhu, Tingshao (Frontiers in Psychology, 2021)
Chinese civilization has a long history, and the Central Plains, with Henan as the core, is one of its birthplaces. Understanding psycho-linguistic changes in Henan is of great significance for understanding the evolution and formation of national cultural psychology. The traditional method is mainly qualitative or speculative, which makes consistency among research results low. Moreover, because most of the research is conducted in a specific period or on a specific figure, it is relatively scattered and unsystematic. To systematically and quantitatively study the psychological changes in the Central Plains represented by Henan Province, this article examined the self-reported discourses of historical celebrities in Henan in official history and their psycho-linguistic changes based on the classical Chinese LIWC psycholinguistic dictionary (Classical Chinese LIWC, CC-LIWC) and the classical Chinese words segmentation system, using big data. The research found that the frequency of male words in Henan historical celebrities (F = 2.938, p <0. 05), of differ words (F = 4.767, p <0. 01), of motion words (F = 4.042, p <0.01), and of time words (F = 5.412, p <0.01) are significantly different among the 5 dynasties. The conclusion is that during the Spring and Autumn and Warring States period, 100 schools of thought contended, and the status of "scholars" in Henan rose. The frequency of male and differ words was at that point significantly higher than during other dynasties. From "The Contention of a Hundred Schools of Thought" to "The Supremacy of Confucianism", the scholars in Henan were in decline, and differential cognitive tendencies had diminished since the Han dynasty. During the period of the Three Kingdoms and Jin and Southern and Northern Dynasties, political powers and territories changed, and historical celebrities in Henan show a remarkable tendency which were relative to time and space. The psycho-linguistic changes found in this study are highly consistent with the development of social history, which indicates that the guidance of the social political and cultural environment has an important influence on the psycho-linguistic changes of social class.